2013
DOI: 10.1111/j.1467-8268.2013.12011.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Integrated Agricultural Research for Development (IAR4D) in the Sudan Savanna of Nigeria

Abstract: This paper assesses the potential economic impacts of Integrated Agricultural Research for Development (IAR4D) conceived to address observed low productivity, prevailing poverty level, slow growth and general underperformance of the agricultural sector associated with the traditional agricultural and rural development (ARD) approach. The economic surplus analysis suggested that IAR4D research and extension, with respect to maize production, could achieve returns ranging from 30 to 38 per cent and a maximum ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
3
7
0
1
Order By: Relevance
“…The result implies that households prefer to diversify their crop production when they do not have access to fertilizer and seed. This is partially because good access to input may lead to specialization in a specific crop and this is in line with the results of Bowman and Zilberman () and Ayanwale et al () who found that agricultural modernization and good access to input can lead to specialization in a specific crop. According to Dorjee et al .…”
Section: Resultssupporting
confidence: 88%
“…The result implies that households prefer to diversify their crop production when they do not have access to fertilizer and seed. This is partially because good access to input may lead to specialization in a specific crop and this is in line with the results of Bowman and Zilberman () and Ayanwale et al () who found that agricultural modernization and good access to input can lead to specialization in a specific crop. According to Dorjee et al .…”
Section: Resultssupporting
confidence: 88%
“…The results are consistent with Aighewi et al (2002) and Mignouna et al (2015) that indicated that quality seed yam unavailability constitutes the major limitation of yam production. Moreover, the BCRs of all the research options imply that investment in research and dissemination of these technologies is worthwhile and economically viable as the benefits greatly outweigh the costs as in agreement with many similar studies on ex ante impact assessment ( Akinola et al, 2009 ; Ayanwale et al, 2013 ; Kostandini et al, 2009 , 2011 ). The NPVs oscillate between US$581 million and US$1392 million with the highest for NRC.…”
Section: Resultssupporting
confidence: 81%
“…Moreover, the BCRs of all the research options imply that investment in research and dissemination of these technologies is worthwhile and economically viable as the benefits greatly outweigh the costs as in agreement with many similar studies on ex ante impact assessment NPV: net present value; IRR: internal rates of return; BCR: benefit-cost ratio; AYMT: adaptive yam minisett technique; NRC: nematode-resistant cultivars; VALSFD: varieties adapted to low soil fertility and drought; CMPP: crop management and postharvest practices; HH: household. (Akinola et al, 2009;Ayanwale et al, 2013;Kostandini et al, 2009Kostandini et al, , 2011. The NPVs oscillate between US$581 million and US$1392 million with the highest for NRC.…”
Section: Resultsmentioning
confidence: 99%
“…Agricultural development can come from different sources; while in the past, the increased use of inputs and the expansion of agricultural land accounted for a large part of agricultural growth in Africa. However, innovation attempts to increase output per unit of input is a major driver of growth (Ayanwale et al ., ). In sub‐Saharan Africa, 63 per cent of the population live in rural areas and are employed in agriculture‐related work (Gildemacher et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…About 90 per cent of Nigeria's food is produced by small‐scale farmers who cultivate small plots of land and depend on rainfall rather than irrigation systems (IFAD, ). However, the role of agricultural innovation in poverty reduction, improving livelihood and enhancing productivity outcomes cannot be over emphasized (Ayanwale et al ., ).…”
Section: Introductionmentioning
confidence: 97%